Over a million students use our free study notes to help them with their homework
this question is a great example as we have many different aspects of a level maths workng together into one.initialy you will use use chain rule to find dy/dx = dy/du * du/dx.then you will either keep th...
f(x) = x3 + 3x V = π ∫ (f(x)2) dx V = π ∫02 (x3 + 3x)(x3 + 3x) dx V = π ∫02 (x6 + 6x4Answered by Zac C. • Maths tutor2913 Views
Differentiate wrt x. This leaves dy/dx = 3x^2 + 6x and equate this to 0 as we are looking for stationary points.So, 3x^2 + 6x = 0. Factorise to get x(3x +6) = 0. So x = 0 and x = -2 are the two solutions....
Re-arrange y-2x-4=0 to y=2x+4Substitute y=2x+4 into 4x^2+y^2+20x=0 to get 4x^2+(2x+4)^2+20x=0Expand the brackets to get 4x^2+(4x^2+16x+16)+20x=0Simplify to get 8x^2+36x+16=0Divide by 4 to get 2x^2+9x+4=0F...
expand the brackets to obtain x^2=4(x^2-6x+9)expand the brackets to obtain x^2=4x^2-24x+36rearrange to obtain 0=3x^2-24x+36factorise to obtain 0=(3x-6)(x-6)solve for x=6 or x=2
←
215
216
217
218
219
→
Internet Safety
Payment Security
Cyber
Essentials